A neglected issue in hospital emergency and disaster planning: Non-standard employment in hospitals. (December 2020) - Tekeli-Yesil, Sidika; Kiran, Sibel
Abstract: Work organization and relationships have changed over recent decades. Following the recent COVID-19 pandemic, the norms concerning work-related standards will likely change even more significantly. There has been a shift away from standard employment to non-standard employment (NSE), which includes fixed-term, part-time, on-call, agency-related employment, dependent self-employment, dispatch, and temporary employment, etc. In nearly every sector. The health sector is no exception. However, the effects of non-standard employment on the disaster preparedness of health systems, particularly on hospitals' emergency and disaster plans, have not yet been adequately studied. Most crucial themes are engagement of non-standard employees in emergency and disaster planning and response, and the impact of non-standard employees in expanding hospitals' capacity in large-scale events. This short communication paper aims to discuss this neglected issue in hospital emergency and disaster planning. In order to see whether NSE is considered in hospital disaster and emergency plans, two hospital disaster and emergency planning guidelines—the Hospital Incident Command System, and the Hospital Emergency Response Checklist developed by the World Health Organization—were assessed regarding NSE in their respective contexts. Although these guidelines are comprehensive tools for hospital preparedness, NSE is not specifically considered in any of them. However, it is essential that NSE, with its trade-offs, is considered in disaster plans to maintain an effective implementation of them. Further research and actions are necessary, especially after the COVID-19 pandemic, to identify how this reflection should be conducted and to supply evidence for further measures and revising emergency and disaster planning guidelines.